2020
DOI: 10.3389/fcell.2020.580131
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning Enhances Cellular Viability and Pro-angiogenic Paracrine Activity: The Roles of VEGF-A and SDF-1a in Rat Adipose Stem Cells

Abstract: To achieve the full therapeutic potential of implanted adipose stem cells (ASCs) in vivo, it is crucial to improve the viability and pro-angiogenic properties of the stem cells. Here, we first simulated the conditions of ischemia and hypoxia using the in vitro oxygen-glucose deprivation (OGD) model and confirmed that hypoxic preconditioning of ASCs could provide improved protection against OGD and enhance ASC viability. Second, we assessed the effect of hypoxic preconditioning on pro-angiogenic potential of AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Several studies indicate that serum-free media may benefit mesenchymal stem cells proliferation, differentiation, and paracrine activity while maintaining their stemness, immunosuppressive and antifibrotic abilities [40][41][42]. In general, secretomes collected under serum-free conditions are much more appropriate for clinical use because of reduced contamination and safety concerns related to xenogeneic infectious agents [43][44][45].…”
Section: Plos Onementioning
confidence: 99%
“…Several studies indicate that serum-free media may benefit mesenchymal stem cells proliferation, differentiation, and paracrine activity while maintaining their stemness, immunosuppressive and antifibrotic abilities [40][41][42]. In general, secretomes collected under serum-free conditions are much more appropriate for clinical use because of reduced contamination and safety concerns related to xenogeneic infectious agents [43][44][45].…”
Section: Plos Onementioning
confidence: 99%
“…It remains a challenge to induce vascularization in engineered tissues by delivering just one growth factor (e.g., VEGF or PDGF-BB). As a key upstream transcription factor, HIF-1α plays important roles in bone tissue engineering via VEGF [ 38 , 39 ] and stromal cell-derived factor 1 (SDF-1) generation to upregulate the VEGF-induced vascularization and SDF-1 induced progenitor cells recruitment [ 40 , 41 ]. HIF-1α and VEGF gene expression levels in Raw 264.7 cells were significantly increased after 24 h of SCS treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown that ASCs generate high concentration of VEGF into the supernatant, especially when cocultured with human umbilical vein endothelial cells or endothelial progenitor cells (14,37). Furthermore, under the hypoxic conditions which imitated the in vivo environment of IHD, ASCs secreted higher amounts of VEGF, HGF, and stromal-derived factor-1 (SDF-1) compared to normoxic conditions (38)(39)(40). The lesion-associated hypoxia, which curbed the survival of engrafted stem cells, would inevitably lead to the activation of hypoxia-inducible factor 1, resulting in increased VEGF release, its classical target gene (41).…”
Section: Is Differentiation Potential the Primary Mechanism Behind As...mentioning
confidence: 99%